An interpretive Proposal for Evaluating Teaching in Higher Education - Edith J. Cisneros-Cohernour (Universidad Autónoma de Baja California, 2008)
This article examines the limitations of the traditional positivist paradigm in the assessment of teaching quality in higher education and proposes the use of an Interpretivist perspective as an evaluative alternative. A case study of a novice college instructor is used for illustrating the limitations of the traditional paradigm and identifying critical issues that take place when the evaluation bases only on student ratings as the only source for determining teaching quality.